Assessing the Azerbaijani Professional Identity Scale for Counselors: An Exploration of Relationships with Professional Identity, Mental Well-Being, Job Satisfaction, and Psychological Distress - Asadov, Fuad; Kazımzade, Cinare; Asgerova, Nigar; Rustamova, Narınj; Nahmatova, Ulviyya; Rustamov, Elnur (Technium Education and Humanities, 2024)
This study introduces the Azerbaijani adaptation of the Professional Identity Scale for Counselors (PISC), exploring its psychometric properties among 206 school counselors in Azerbaijan. Utilizing Confirmatory Factor Analysis (CFA), the scale’s original four-dimensional structure was validated, aligning closely with its intended design. Reliability analyses across both subscales and the overall scale demonstrated high levels of consistency, underscoring the tool’s robustness. Criterion-related validity was established through meaningful correlations with mental well-being, job satisfaction, and psychological distress, aligning with anticipated directions. Notably, psychological distress was found to mediate the relationships between professional identity and both mental well-being and job satisfaction, highlighting the complex interplay between professional identity, psychological health, and workplace satisfaction among counselors. This study not only confirms the reliability and validity of the Azerbaijani PISC but also sheds light on significant associations that underscore the importance of professional identity in the mental health and job satisfaction of school counselors.